2023
DOI: 10.1101/2023.10.16.562535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid establishment of species barriers in plants compared to animals

François Monnet,
Zoé Postel,
Pascal Touzet
et al.

Abstract: Speciation, the process by which new reproductively isolated species arise from ancestral populations, occurs because of genetic changes that accumulate over time. To date, the notion that interspecific genetic exchange occurs more frequently between plant species than animals species has gained a strong footing in the scientific discourse, albeit primarily relying on verbal arguments centered on mating behavior. By examining the dynamics of gene flow across a continuum of divergence in both kingdoms, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…In particular, it will be exciting to determine how different groups of organisms accumulate such incompatibilities, especially since the "speciation clock" has been suggested to tick at different paces across the tree of life (e.g. in plants vs animals, Monnet et al, 2023). In addition, here we focused on the male germline, but the comparison with the female germline would be necessary to provide a comprehensive picture.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it will be exciting to determine how different groups of organisms accumulate such incompatibilities, especially since the "speciation clock" has been suggested to tick at different paces across the tree of life (e.g. in plants vs animals, Monnet et al, 2023). In addition, here we focused on the male germline, but the comparison with the female germline would be necessary to provide a comprehensive picture.…”
Section: Discussionmentioning
confidence: 99%
“…The DILS pipeline allows the analysis of two species scenarios only: we therefore performed separate analyses for the three two-species comparisons, with the "all-CS", "all-CV", and "all-SV" pairwise datasets. We first tested the priors proposed by Monnet et al (2023) according to observed statistics of polymorphism and divergence: we then increased the range of priors to get better results on the goodness-of-fit tests. We used the same priors for all analyses, with different numbers of sequences per gene and per sample according to the dataset (Table S4).…”
Section: Scenarios Of Speciationmentioning
confidence: 99%